Efektivitas Core Value Berakhlak Dalam Meningkatkan Kepribadian Pegawai: Studi Pada Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Kota Banjar - Ading Achmad Sjafjudin (GEMILANG: Jurnal Manajemen dan Akuntansi, 2023)
This study aims to analyze and find out (1) the effectiveness of the implementation of the AKHLAK Core Values, (2) Obstacles or obstacles to the implementation of the AKHLAK Core Values, and (3) solutions to further streamline the implementation of the AKHLAK Core Values ​​in an effort to improve the personality of Employees at the Personnel and Human Resources Development Agency. Banjar City Man. The method in this study is to use a qualitative descriptive type. The description method is a method in researching the status of human groups, an object, a set of conditions, a system of thought, or a class of events in the present. Researchers collected data using interviews, observation, and documentation for 3 months. Based on the results of the study it was found that the implementation of the Core Values ​​of BerAKHLAK at the Personnel and Human Resources Development Agency for the City of Banjar to improve the personality of employees at work was very good, so that the personality of the employees became better.